SHE can't afford it and HE doesn't want it: The gender gap in the COVID-19 consumption response - Stefanie Huber (Tinbergen Institute, 2022)
This paper explores whether and why the pandemic differentially altered women and men\~As consumption behavior. After the 2020 wave of lockdown restrictions were lifted, women reduced consumption more than men. Data on self-reported reasons for consuming less reveals that gender differences in infection risk aversion and precautionary saving motives are small. I find consider- able gender differences in the reporting of affordability constraints and consumer preference shifts. Women report financial constraints more frequently. Men adapted more to the limited consumption possibilities during the lockdown and frequently reported \~A'not missing\~A" various items as the primary reason for spending less than pre-pandemic.
Keywords: D12; D14; D30; E21; G50; J16; 330; COVID-19; gender gap; gender equality; household consumption; consumer preferences; experience effects; fiscal policy